THE SIGNIFICANCE OF GENERAL PEDAGOGICAL FLEXIBILITY AND SKILLS IN LANGUAGE DEVELOPMENT (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article deals with pedagogical flexibility and skills as part of the content of modern school education. The concepts of «flexibility», «skills» are defined. The importance of building the learning process in accordance with life experience is determined, with a focus on the practical application of theoretical knowledge gained in the classroom.In addition to theoretical knowledge of linguistics in elementary school, the development of mental skills, the skills to perform logical operations, is of great importance. It has been proven that pedagogical flexibility and skills help the student to effectively carry out educational activities, acquire in-depth knowledge, adapt the acquired knowledge to any new situation, and conduct a creative search.
Keywords: general pedagogical flexibility, skills, language development, elementary school.